Biorremediação de solo contaminado com óleo lubrificante pela aplicação de diferentes soluções de surfactante químico e biossurfactante produzido por Pseudomonas aeruginosa LBI - Lopes, Paulo Renato Matos [UNESP] (2014)
Environmental impacts with petroleum and its derivatives cause considerable damage and a huge public concern pressing for quick and economic solutions. According to alternatives treatment for hydrocarbons contamination, bioremediation represents a viable process to maintain the ecological balance. Also, a better efficiency in biological treatment is achieved by adopting strategies such as bioaugmentation and application of surfactants, whose properties increase the hydrophobic compounds bioavailability. Thereby, biosurfactants become appropriated to substitute synthetic since their advantages: high structural diversity, low toxicity and high biodegradability. Despite the many benefits presented by biosurfactants, they are not commercially used due to the high production cost. The purpose of this study was to evaluate the biodegradation of waste automotive lubricant oil in soil by application of different surfactants solutions (chemical and biosurfactant produced by Pseudomonas aeruginosa LBI from an agroindustrial residue). Besides, the efficiency of bioremediation process was analyzed as: microbial metabolism, physico-chemical parameters, ecotoxicity and diversity of microbial community. Initially, the results showed that P. aeruginosa LBI was able to produce rhamnolipids from soybean soapstock. In biodegradation process, surfactants and bioaugmentation improved the microbial activity. Therefore, the biological treatment increased CFU number for bacteria and fungi and it was able to reduce phytotoxic effects and heavy metals concentration in relation to original contamination. Likewise, microbial community dynamics during bioremediation set a different profile when it was compared with the initial time. However, treatments with chemical detergent had low microbial amount and high phytotoxicity even after 180 days. Thus, the combination of bioaugmentation and Tween80 or rhamnolipid applications were effective and environmentally viable...